Endovascular Bail Out for a Failed Transcatheter Aortic Valve Implantation in High Surgical Risk Patient. (9th March 2021) - Peluttiero, Ilaria; Robaldo, Alessandro; Leotta, Luigi; Novali, Claudio
Abstract : The endovascular treatment for acute type A dissection (ATAD) represents an alternative and emerging option in selected high surgical risk patients. We report a successful total endovascular ATAD repair occurred intraoperatively during transcatheter aortic valve implantation (TAVI) placement in 82 years old female, not fit for surgery in emergency setting. The presentation, the diagnostic evaluation, and the technique are discussed. This case would support the feasibility and efficacy of the stent graft technology to treat ATADs after evaluation of clinical, anatomical, and radiological parameters.